Agricultural expansion and tropical deforestation poverty, international trade and land use - Barraclough, Solon L; Ghimire, Krishna B (London Earthscan, 2000)
Agricultural expansion and tropical deforestation puts the case for the need to seek solutions in far-reaching institutional and policy reforms at local national and international levels ,if the real challenges of tropical deforestation are to be tackled
Keywords: Deforestation; International trade; Agriculture and state; Commercial policy; Poverty